Tinjauan Kelengkapan Isi Rekam Medis Pada Formulir Resume Medis Kasus Bedah di Rumah Sakit Haji Pondok Gede Jakarta Pada Tahun 2017 - Sri Ani; Wiwik Viatiningsih (Lembaga Penerbitan Universitas Esa Unggul, 2015)
Abstract Discharge Summary is the information contained in the home history summary is a summary of all patient care and treatment periods that have been pursued by health workers and related parties. This sheet should be signed by the treating physician. The completeness of the medical resume is used for the basis of internal and external hospital reporting, the decision evaluation is expected to be better in making further treatment plans, and to support the orderly administration. The research method used is descriptive analysis method and data collection technique is observation, quantitative analysis, and interview guidance. Based on the results of research on Standard Operational Procedures of filling medical resume at Haji Pondok Gede Hospital Jakarta already exist, where Standard Operational Procedure of medical resume fill 2X24 Hours after patient come home with standard completion of medical resume 100%, and Based on result of quantitative analysis of 102 medical resume surgical case, resume completeness is 80%. Factors causing incompleteness in filling out medical resume form of surgical case that is Doctors have a busy schedule, Policy and discipline level of medical resume filling less socialized. The need to re-socialize the Standard Operating Procedures of medical resume filling and need assertiveness from the Director of the Hospital for the level of discipline in filling the medical resume can be done well and on time.Keywords: Medical Discharge, Filling Complete, Case Surgery